1999
DOI: 10.1038/sj.ijo.0800891
|View full text |Cite
|
Sign up to set email alerts
|

Leptin concentrations during oral glucose tolerance test (OGTT) in obese and normal weight women

Abstract: OBJECTIVE: To examine possible changes of leptin concentrations after the acute administration of glucose orally (OGTT). DESIGN: Seventy-®ve grams of glucose were administered per os in one group of obese and normal weight individuals and concentrations of glucose, insulin and leptin were measured at 0, 30, 60, 90 and 120 min. In an age matched control group of individuals with similar BMI water was given and leptin concentrations were measured before and after 30, 60, 90 and 120 min. SUBJECTS: Twenty-seven ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
6
8
2
1
Order By: Relevance
“…Our observation agrees with a previous report [14], indicating that basal leptin levels were not correlate with those of glucose. No significant changes in leptin levels were found in normal weight women after glucose administration [14]. There is evidence that surgical stress increases fasting blood sugar levels [2,15,16].…”
Section: Discussionsupporting
confidence: 83%
“…Our observation agrees with a previous report [14], indicating that basal leptin levels were not correlate with those of glucose. No significant changes in leptin levels were found in normal weight women after glucose administration [14]. There is evidence that surgical stress increases fasting blood sugar levels [2,15,16].…”
Section: Discussionsupporting
confidence: 83%
“…59 Furthermore, hyperinsulinemia is related to the production of free radicals. [60][61][62][63] CRP, and other parameters, such as leptin, resistin, TNF-α, and IL-6, were high in obese women prior to intervention as previously reported by our group.…”
Section: Discussionsupporting
confidence: 56%
“…This observation corresponds to our univariate negative association with HOMA insulin sensitivity. In other studies significant differences were found between obese and non-obese participants such that the latter group had no change while the former showed an increase in serum leptin levels during an OGTT [12,14]. Although we found a decrease in healthy subjects and no change in glucose intolerant women, these finding are not inconsistent with those of other studies which may be confounded by other factors (i.e.…”
Section: Study Limitations and Strengthscontrasting
confidence: 60%